The English problem : a novel - Kamlani, Beena (Crown, 2025)
"The English Patient meets EM Foster, The English Problem is a stunning debut that looks at the insidiousness of colonialism and one young man's sexual awakening. In 1931 a young man from India arrives in London. Ten years later he will be on a ship bound for India, in a coma, accompanied by a nurse. But that is a decade away For now, in 1931 he is not dressed for the British rain, and shivering, rings the doorbell of the people who have agreed to host him during his stay in this strange land. He finds that his hosts are having a party and warmly welcome him in. He is the only Brown person in the room. It is the first time for what will become an everyday experience"--